The significance of post-mortem vitreous calcium concentration in forensic practice. (November 2020) - Mihailović, Zoran; Popović, Vesna; Durmic, Tijana; Milošević, Miroslav; Soldatović, Ivan; Radnić, Bojana; Atanasijević, Tatjana
Highlights: Vitreous humor (VH) is one of the most useful samples for postmortem chemical analysis. Repetitive VH sampling enables detailed insight in the postmortem calcium metabolism. Calcium concentration in VH cannot be used as the only PMI predictor. Abstract: Calcium, as one of the main extracellular ions, maintains a key role in numerous biologic functions. For forensic purposes, it was analyzed mostly for estimation of postmortem interval (PMI). We have designed our experiment with the concept that the repetitive withdrawal of vitreous humor (VH) might clarify the postmortem metabolism of calcium in greater detail to estimate the PMI. Accordingly, 248 samples of VH from 31 autopsy cases were evaluated over three years; samples (0, 1 mL of VH) were taken and analyzed at equal time intervals after death—every three hours until 24 h after death. Each sample was centrifuged and analyzed using the ARCHITECT C SYSTEM 8000. Moreover, functional relationship between PMI and calcium concentration was established: PMI (hours) = [Ca 2+ ] × 13.696–7.843. Although the concentration of calcium in VH in the analyzed group increases with time, the coefficient of variation for the regression (CVreg = 46.8%) indicates that this correlation is not so strong, meaning that the level of predictiveness of calcium for estimation of time since death is poor when is not used in combination with other relevant substances.